Culture of Pleurotus ostreatus in pine shavings: isolation of strains and evaluation of their productivity - Mata, Gerardo; Pérez-Torres, José Antonio; Medel, Rosario; Pérez-Merlo, Rosalía; Salmones, Dulce (Instituto de Ecología, A.C., 2019)
In order to obtain strains of the edible mushroom Pleurotus ostreatus that can be cultivated in pine wood shavings, 36 monosporic cultures were isolated and propagated in vitro, selecting 6 cultures of rapid mycelial growth in order to obtain interspecimen crosses and dikaryon-monokaryon mating. Eleven of the crosses obtained and their 6 parental strains were cultured in vitro in order to determine their growth in pine shavings and barley straw (control), selecting 6 strains (3 crosses, 3 parental strains) for sporome production in the two growth substrates. At in vitro level, significant differences were found between the mycelial areas of monokaryons and dikaryons in the treatments (time, substrate) evaluated. In terms of sporome productivity, the cultures in barley straw presented higher biological efficiency (22.6%-46.4%) and production rate (0.31%-0.77%) values than those in the pine shavings (3.3%-12% and 0.03%-0.11%, respectively). Sporome pileus diameters of 5 cm to 9.9 cm were the most frequent in both substrates. In general, the crosses surpassed their parents in both mycelial growth and sporome production, although further study is required in order to facilitate increased productivity of the strains in this potentially useful agroforestry residue.